2020
DOI: 10.1111/zph.12714
|View full text |Cite
|
Sign up to set email alerts
|

Personal and household factors involved in recentRickettsiaexposure in a rural population from Yucatán, Mexico

Abstract: The aim of the study was to describe the epidemiological factors associated with the risks of recent Rickettsia exposure in inhabitants of a rural population from Yucatán, Mexico. The study included 130 inhabitants from Maxcanú, Yucatán. Blood samples were collected to detect IgM and IgG antibodies against Rickettsia typhi and Rickettsia rickettsii by an indirect immunofluorescence antibody test. Additionally, nested polymerase chain reaction was performed to amplify fragments of the 17kDa and sca5 genes. Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 43 publications
0
9
0
6
Order By: Relevance
“…This finding may also be associated with early infection with Rickettsia spp. as is the bacteremia (Torres‐Castro et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding may also be associated with early infection with Rickettsia spp. as is the bacteremia (Torres‐Castro et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As part of an ongoing study to identify the eco‐epidemiology of rickettsiosis in Southeastern Mexico, whole blood samples were collected from 130 people distributed in 60 households in the rural community of Maxcanu (20°33′, 20°46′N–89°53′, 90°24′W) where an active focus of murine typhus is present (Figure 1). Blood samples were taken by qualified health personnel (Torres‐Castro et al., 2020). Maxcanu has an altitude of 10 m above sea level with an average annual temperature of 27.4ºC, and an annual rainfall of 1080 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies in a rural locality in the State of Yucatan, Mexico, performed by Torres-Castro et al [ 18 , 19 , 20 ], found that 90% of the people exposed to Rickettsia sp. infection (antibodies) were dog owners, and 70% had more than one dog in their household.…”
Section: Introductionmentioning
confidence: 99%
“…Since people from Maxcanú showed exposure to TG Rickettsia [ 18 ], and there is evidence of R . typhi infecting domiciliated dogs in the studied region [ 9 , 10 , 21 ], this research addresses the following questions: what is the occurrence of the TG Rickettsia natural infection in domiciliated dogs?…”
Section: Introductionmentioning
confidence: 99%